Post-Communist Rule of Law in Post-Democratic European Union. A sceptical legal sociologist’s reflections on European Unity - Adam Czarnota (Sortuz)
It is quite difficult to write about the topic of European political unity. Few years ago discussion has started and Europe is still dreaming on potential political unity. Particular states are declaring their positions and changing their opinion depending of current political and economic climate. From legal point of view the problem of European unity is encapsulated in an idea of constitutionalisation of Europe. The process to write a constitutional treaty has been derailed, and at present, European Union live in institutional setting of the Lisbon Treaty. It is also not easy to write about the so-called eastern part of EU after double enlargements. There are different perspectives one can adopt. One possibility is the perspective of an Eastern European. The second is to look from the perspective of a Western European. It is also possible to adopt a third perspective, that of a sympathetic external observer. In the end I decided to adopt a different approach: not the position of an impartial judge, not the position of a prosecutor or defence lawyer but that of a sceptical lawyer close to what is known in legal procedure as an expert witness. I will argue that Eastern Europeans always wanted to join Europe, but a Europe from the past not the European Union of the present. Then I will look at the issues connected with the relationship between enlargement and constitutionalisation in the European Union. I will finish with some sceptical remarks as far as prospects for European rule of law are concerned.